A pernicious cycle: Finding the pathways from child maltreatment to adolescent peer victimization. (July 2018) - Yoon, Dalhee; Yoon, Susan; Park, Jiho; Yoon, Miyoung
Abstract: The purpose of this study was to identify the pathways from childhood physical and sexual abuse to adolescent physical and sexual victimization by assessing behavior symptoms (both internalizing and externalizing) and peer popularity as potential mediating variables. The data derive from Longitudinal Studies of Child Abuse and Neglect (LONGSCAN), which tracks the consequences of child abuse and neglect using five study sites across the US. Child physical and sexual abuse was measured at age 12 using self-reports of life-time maltreatment experiences. Internalizing and externalizing symptoms were assessed at age 12 using the Child Behavior Checklist (CBCL). Peer popularity was assessed at age 14 by teachers. Peer victimization was assessed at age 16 using the modified version of the Juvenile Victimization Questionnaire. The results indicated that physical abuse had no direct effect on either physical or sexual peer victimization, whereas sexual abuse had significant direct effect on both physical and sexual victimization. Assessed at age 12, children who had been physically or sexually maltreated were found to have higher levels of internalizing and externalizing symptoms. These increased symptoms are associated with lower peer popularity at age 14, which in turn is associated with greater physical and sexual peer victimization at age 16. The findings suggest that multiple points for interventions may exist to disrupt the cycle of victimization. Early assessment and treatment for externalizing symptoms and for low peer popularity may be helpful in preventing physical peer victimization among adolescents who have been physically and/or sexually abused.